Two microporous CoII-MOFs with dual active sites for highly selective adsorption of CO2/CH4 and CO2/N2. Issue 36 (30th August 2019) - Ma, Hui-Yan; Zhang, Yong-Zheng; Yan, Hui; Zhang, Wen-Jie; Li, Yun-Wu; Wang, Su-Na; Li, Da-Cheng; Dou, Jian-Min; Li, Jian-Rong
Abstract : Two microporous Co II -MOFs exhibit highly CO2 /CH4 and CO2 /N2 selective adsorption owing to abundant dual active sites. GCMC theoretical simulations further verify the experimental results. Abstract : Simultaneously involving abundant [NH2 (CH3 )2 ] + cations and uncoordinated carboxylate oxygen atoms as dual active sites, two microporous Co II -MOFs (LCU-105 and LCU-106, LCU = Liaocheng University) both exhibit highly selective adsorption of CO2 /CH4 and CO2 /N2 . GCMC theoretical simulations provide good verification of the experimental results.